Osteosarcoma with Orbital Metastasis in a Nigerian Child: A Case Report and Review of the Literature - Adekunle MO; Diaku-Akinwumi IN; Akinola AO; Akinyosoye G (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Osteosarcoma is the most common primary bone tumour with a peak occurrence in adolescence. The occurrence of osteosarcoma in preadolescents is rare with a paucity of data in the developing world. Metastasis of osteosarcoma to the orbit is even a rarer presentation with few cases reported in the literature but to the best of the researchers' knowledge, none of the previous cases had contralateral orbital metastasis to osteosarcoma. This is the first case report of orbital metastasis of osteosarcoma in Nigeria. The present case is presented for its rarity, to increase awareness and add to knowledge on the possibility of metastasis to contralateral orbit in osteosarcoma.